Analysis of The Influence of Working Capital, Liquidity and Solvency on Profitability in The Mining Industry Listed on The Indonesia Stock Exchange (Idx) For The Period 2020-2024 - Novridanty Pongpare; Alfiana Antoh; Yulianti Karoma (Journal of International Conference Proceedings, 2025)
This study aims to analyze the influence of working capital, liquidity, and solvency on profitability in the mining industry listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The research method used is a quantitative approach using secondary data in the form of annual financial statements of 25 mining companies for five years, resulting in a total sample of 125 samples. The data analysis technique used was multiple linear regression based on panel data which was analyzed using the EViews 12 application. The results of the study show that working capital (WCT) positively has no significant effect on profitability (NPM), liquidity (CR) negatively does not have a significant effect on profitability (NPM), while solvency (DAR) has a significant effect on profitability (NPM), working capital variables, liquidity and solvency have a significant effect on company profitability simultaneously. The adjusted R square value of 4.27% indicates that working capital, liquidity, and solvency together explain only a small fraction of the variation in profitability, while the rest is influenced by other factors outside of this study.